Zooplankton Diversity and Pelagic Food Webs Investigating Present and Past with Different Techniques - Piscia, Roberta; Bettinetti, Roberta; Leoni, Barbara; Manca, Marina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Zooplankton are of key importance in the structure and functioning of aquatic food webs. They contribute to a large part of the functional and structural biodiversity of predator and prey plankton communities. Promptly responding to long-term and seasonal changes in the physical and chemical environment, they are sensitive indicators of patterns and mechanisms of impact drivers, both natural and human induced. In this volume, we aim to present evidence for both long-term and seasonal changes in zooplankton community structure and dynamics, investigating different approaches from population dynamics to advanced molecular techniques and reconstructing past communities from subfossil remains in lake sediments.